Intra and inter-annual patterns in Lake Yojoa, Honduras: disentangling biogeochemical drivers of a tropical monomictic lake ecosystem - Fadum, Jemma Mazuri, author; Hall, Ed, advisor; Wrighton, Kelly, committee member; Ross, Matt, committee member; Burgin, Amy, committee member (Colorado State University. Libraries, 2022)
To view the abstract, please see the full text of the document.
Keywords: biogeochemistry; trophic state; aquaculture; tropical lake; nitrogen